Comparative Evaluation Of Topical Preparations In Treatment of Melasma - Pandhi Roma; Kaur I; Handa S (Wolters Kluwer Medknow Publications, 2002)
Fifty patients of melasma were randomly taken up for the study and were divided into five treatment groups of 10 patients each. Patients of these groups received clobetasol propionate 0.05% (group I), tretinoin 0.025% (group II), hydroquinone 2% (group III), bebzoyl peroxide 5% (group IV) and glycolic acid 10% (group V). Pretreatment evolution was done with MASI (melasma area severity index) scoring and photographic records. Patients were treated for 3 months and the preparations were found to be equally compatible to our patients. However, effectiveness on an average was higher for clobetasol (80%) and tretinoin (62%), though hydroquinone (48%), benzoyal peroxide (41%) and glycolic acid (30%) also showed fairly good results. Our study broadens the therapeutic spectrum of melasm by using agents with different mechanisms of action.